2013
DOI: 10.1053/j.ajkd.2013.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pre-existing Vascular Pathology With Arteriovenous Graft Outcomes in Hemodialysis Patients

Abstract: Background Arteriovenous grafts (AVGs) are prone to neointimal hyperplasia leading to AVG failure. We hypothesized that pre-existing pathologic abnormalities of the vessels used to create AVG (including venous intimal hyperplasia, arterial intimal hyperplasia, arterial medial fibrosis, and arterial calcification) are associated with inferior AVG survival. Study Design Prospective observational study. Setting & Participants Patients with chronic kidney disease undergoing placement of a new AVG at a large me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
2
28
4
Order By: Relevance
“…Similarly, greater medial fibrosis or microcalcification of arteries was associated with a lower frequency of AVG interventions. In contrast, none of the above variables (arterial IH, venous IH, severe arterial medial fibrosis, and severe arterial calcification) were able to predict primary unassisted patency or the time to first access intervention (55). The lack of association of preexisting vascular pathology with primary unassisted AVG patency might indicate that the study was underpowered.…”
Section: Preexisting Vascular Pathology and Avg Outcomesmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, greater medial fibrosis or microcalcification of arteries was associated with a lower frequency of AVG interventions. In contrast, none of the above variables (arterial IH, venous IH, severe arterial medial fibrosis, and severe arterial calcification) were able to predict primary unassisted patency or the time to first access intervention (55). The lack of association of preexisting vascular pathology with primary unassisted AVG patency might indicate that the study was underpowered.…”
Section: Preexisting Vascular Pathology and Avg Outcomesmentioning
confidence: 87%
“…Published investigations have shown no association between individual arterial or venous histopathologic findings and access outcomes in relatively small cohorts. The only two studies that simultaneously assessed multiple preexisting conditions on preaccess arteries failed to report any potential interaction between two or more of these vascular pathologies and vascular access outcomes (38,55). However, studies that integrate the potential effect of multiple venous pathologies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these therapies will be limited to prevent postsurgical NIH and not preexisting neointimal lesions in the vein. The existence of preexisting NIH in veins of hemodialysis patients has been recently described, and its presence is not associated with A-V fistula outcomes (1,3,24). …”
Section: Discussionmentioning
confidence: 98%
“…A second study found no association of preexisting arterial medial fibrosis or arterial calcification with AVF nonmaturation (18). In contrast, a third study observed a lower frequency of arteriovenous graft (AVG) interventions in patients with preexisting arterial or venous pathology, suggesting a protective effect against neointimal hyperplasia in vascular access (24). These contradictory findings suggest that the cellular mechanisms leading to neointimal hyperplasia after AVF creation differ from those leading to the preexisting ;vascular abnormalities in uremic patients.…”
mentioning
confidence: 96%